IMMINENT RELEASE OF THE DEPARTMENT OF TRANSPORTATION STUDY OF AIRCRAFT CABIN AIR QUALITY (Tufts Archival Research Center, 2007)
Memorandum from Sam Chilcote to the Tobacco Institute executive committee regarding the release of a Department of Transportation (DOT) study on aircraft cabin air quality and smoking. States the industry's position to oppose any additional in-flight smoking restrictions. Applauds the Institute's success thus far in delaying or eliminating added regulation. Discusses plans to develop a response to the DOT study.